Leaders Build Cultures: Action Steps for Leaders to Build Successful Organizational Cultures - Warrick, D. D.; Gardner, Donald G. (Journal of Leadership, Accountability and Ethics, 2021)
The ability to build strong cultures is a critical skill for leaders, and should be a top priority for their training, development, and education. This article addresses the need for leaders at all levels of an organization to be skilled at building cultures capable of achieving excellent results and bringing out the best in people, and offers specific advice on how to do so. The article draws from the extensive research available on building cultures and also includes lessons learned from the legendary turn-around of the culture and resulting success of Ford Motor Company by former CEO Alan Mulally.